Dukungan Keluarga dalam Meningkatkan Motivasi Belajar Siswa - Lailatuzzahro Al-Akhda Aulia; Estalita Kelly; Ahmad Sarifudin Zuhri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Education has a very important role for the advancement of a nation. The pandemic period that occurred had an impact on all aspects of life, one of them in education. It is undeniable that the online learning system implemented has an impact on student learning motivation. Learning motivation will provide enthusiasm so the student will be know the direction of learning. The phenomenon of low learning motivation which is increasing during pandemic has finally become important to discuss. The purpose of this research is to determine the role of family support on student’s learning motivation during pandemic. The research method is quantitative method. The research variables were measured using psychological scale, there is learning motivation scale consists of 26 items with a reliability coefficient of 0,743 and family support scale consists of 30 items with a reliability of 0,880. The research subjects were 75 respondents who were taken using the accidental sampling technique. The data obtained were analyzed using simple regression analysis. Data analysis results showed F = 14,339 with p = 0,00 which means that there is a role of family support on students’ learning motivation, with a contribution of 16,4%. Coefficient of regression is positive, so it can be concluded that family support has a positive effect on increasing learning motivation.Pendidikan memiliki peranan yang sangat penting bagi kemajuan suatu bangsa. Masa pandemi yang terjadi memberikan dampak pada seluruh aspek kehidupan, salah satunya dalam pendidikan. Tidak dapat dipungkiri jika sistem pembelajaran daring yang diterapkan memberikan dampak kepada motivasi belajar siswa. Adanya motivasi akan memberikan semangat sehingga siswa akan mengetahui arah belajar. Fenomena motivasi belajar rendah yang semakin meningkat di masa pandemi ini pada akhirnya menjadi penting untuk dibahas. Penelitian ini dilakukan dengan tujuan untuk mengetahui peran dukungan keluarga terhadap motivasi belajar siswa di masa pademi. Metode penelitian yang digunakan adalah metode kuantitatif. Variabel penelitian diukur dengan menggunakan skala psikologi yaitu skala motivasi belajar yang berjumlah 26 aitem dengan koefisien reliabilitas sebesar 0,743 dan skala dukungan keluarga yang berjumlah 30 aitem dengan koefisien reliabilitas sebesar 0,880. Subjek penelitian adalah 75 responden yang diambil dengan menggunakan teknik accidental sampling. Data yang diperoleh dianalisis dengan menggunakan analisis regresi sederhana. Hasil analisa data menunjukkan F = 14,339 dengan p = 0,000, artinya ada peran dukungan keluarga dalam meningkatkan motivasi belajar siswa, dengan sumbangan sebesar 16,4%. Koefisien korelasi bernilai positif, dapat disimpulkan jika dukungan keluarga memberikan pengaruh secara positif dalam meningkatkan motivasi belajar.